Timing and intraindividual variability of daytime napping and Alzheimer’s disease in older adults - Chenlu Gao; Xi Zheng; Ruixue Cai; Lei Yu; Julie A. Schneider; Aron S. Buchman; David A. Bennett; Yue Leng; Agustin Ibáñez; Lei Gao; Kun Hu; Peng Li (Communications Medicine)
Abstract Background Excessive daytime napping has been associated with neurodegeneration in older adults, but prior research has focused on nap duration and frequency. Emerging frameworks emphasize the multidimensionality of sleep, but it remains unknown whether other dimensions of napping (e.g., timing, variability) are linked to neurodegeneration. To address this gap, we investigated the associations of daytime nap timing and intraindividual variability of nap duration with incident Alzheimer’s dementia and Alzheimer’s disease pathology. Methods We analyzed data from 936 older adults (age range: 56–99; 77% female) in the Rush Memory and Aging Project to examine incident Alzheimer’s dementia and from 320 deceased participants (age range at death: 71–105; 70% female) to examine Alzheimer’s pathology. The proportions of morning (9–11am) and early afternoon naps (1–3 pm) and the intraindividual variability of nap duration were assessed using actigraphy. Participants completed neurological assessments at baseline and annually for up to 17 years. In deceased participants, amyloid β and neurofibrillary tangles were examined. Results Here we show that more morning naps are linked to a higher risk of Alzheimer’s dementia, whereas more early afternoon naps are linked to reduced amyloid β levels. Higher intraindividual variability of nap duration is shown to be associated with increased amyloid β and neurofibrillary tangles. Conclusions Our findings suggest that specific timing patterns and irregularities in daytime napping are linked to Alzheimer’s disease risk and pathology. Multi-dimensional assessments of nap behaviors may aid in risk stratification for neurocognitive impairment and offer a potential target for interventions aimed at promoting healthy cognitive aging.